2016
DOI: 10.1002/14651858.cd001829.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating oral leukoplakia to prevent oral cancer

Abstract: cancer survival longer than five years after diagnosis are low. Drugs, surgery and other therapies have been tried for treatment of oral leukoplakia. Objectives This review aimed to evaluate whether treatments for oral leukoplakia are effective in preventing oral cancer, and safe and acceptable to patients. Study characteristics The evidence on which this review is based is up-to-date as of May 2016. We found 14 randomised controlled trials (RCTs) of medical and complementary treatments, which involved 909 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
165
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 68 publications
1
165
3
2
Order By: Relevance
“…A recent Cochrane review concluded that there was insufficient evidence to validate any intervention in the treatment of leukoplakia, including surgical modalities. This was due to the fact that there have been no randomised clinical trials assessing the effect of surgical excision on the development of oral cancer that include a control arm with no treatment, due to the associated ethical issues . The position can certainly be argued that lesions displaying any grade of OED should, where possible, be excised and this approach has mostly been taken with the current cohort under investigation …”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review concluded that there was insufficient evidence to validate any intervention in the treatment of leukoplakia, including surgical modalities. This was due to the fact that there have been no randomised clinical trials assessing the effect of surgical excision on the development of oral cancer that include a control arm with no treatment, due to the associated ethical issues . The position can certainly be argued that lesions displaying any grade of OED should, where possible, be excised and this approach has mostly been taken with the current cohort under investigation …”
Section: Discussionmentioning
confidence: 99%
“…Often times, patients present with multifocal non‐contiguous lesions (PVL) with a histopathological diagnosis of “hyperkeratosis no dysplasia,” yet 70%–100% will develop cancer over time. Current strategies for oral leukoplakia include surgery, a “watch‐and‐see” approach, and medical treatment (Farah et al., ; Lodi et al, ; Ribeiro, Salles, da Silva, & Mesquita, ). Recurrence after surgical excision ranged from 0% to 35% (Holmstrup et al., ; Lumerman et al., ; Pindborg, Jolst, Renstrup, & Roed‐Petersen, ; Silverman et al., ; Vedtofte, Holmstrup, Hjorting‐Hansen, & Pindborg, ); 0%–15% when carbon dioxide laser was used; and 10%–25% in patients who underwent photodynamic therapy (Vohra et al., ).…”
Section: Management Of Oral Leukoplakiamentioning
confidence: 99%
“…The incidence varies across the world and is high in Central and Eastern Europe, Hong Kong, India, and Brazil, and among African Americans in the USA . Although most OSCC develop de novo, with no preceding potentially malignant lesions, many cases of OSCC originate from oral erythroplakia and leukoplakia (OEL), the most common oral potentially malignant lesions (OPML) . Prevention of OEL malignant transformation may improve the outcome of OSCC, through the identification of OEL at high risk of malignant transformation, and the use of chemopreventive agents to address the field of cancerization .…”
Section: Introductionmentioning
confidence: 99%